GE_GERICHTE C/1232/2013 vom 11. September 2015 - GE Cour de justice (2015)
MANDAT; RESPONSABILITÉ CONTRACTUELLE; DILIGENCE; OBLIGATION DE RENSEIGNER; LIEN DE CAUSALITÉ; FAUTE DU TIERS | CO.44.1; CO.97; CO.394.2;